False lumen intervention to promote remodelling and thrombosis—The FLIRT concept in aortic dissection. Issue 4 (30th March 2018) - Yuan, Xun; Mitsis, Andreas; Semple, Thomas; Castro Verdes, Mireya; Cambronero‐Cortinas, Esther; Tang, Yida; Nienaber, Christoph A.
Abstract: Objective: Thoracic endovascular aortic repair (TEVAR) has changed the management of aortic dissection by induced remodelling. Beyond reconstructing the true lumen, we describe the concept of False Lumen Intervention to promote Remodelling and Thrombosis (FLIRT) in both type A and B aortic dissection. Methods: Between 2011 and 2017, 10 patients with aortic dissection (5 type A; 5 type B) underwent FLIRT using a combination of patent foramen ovale (PFO) or atrial septal defect (ASD) occluders, coils and glue. Patients were followed by computed tomography (CT) angiogram prior to, and 6 months following, discharge to evaluate false lumen (FL) thrombosis and aortic remodelling. Outcomes analyzed comprised successful device delivery, completeness of FL thrombosis and aortic remodelling, procedure related complications and mortality. Results: FLIRT induced aortic remodelling in all cases of proximal dissection, with aortic shrinkage from 63.8 ± 7.5 pre‐FLIRT, to 50.2 ± 6.6 mm ( P = 0.057) and an increase in true lumen area from 5.8 ± 3.6 to 11.4 ± 2.5 cm 2 ( P = 0.006). In distal dissection (after previous TEVAR with residual FL flow), FLIRT successfully induced FL thrombosis in 4 of 5 cases at first attempt (1 case required additional coiling of the gutter between left subclavian artery and stent‐graft for complete thrombosis). While maximal aortic diameter remained unchanged (55.6 ± 9.1 pre‐FLIRT and 54.4 ± 13.7 mm at follow‐up), true lumen area increased from 7.8 ± 2.3 pre‐procedure, to 10.6 ± 1.5 cm 2 at follow‐up ( P = 0.016), consistent with remodelling. Conclusion: Interventional FL management, using the FLIRT concept, is feasible in selected cases of aortic dissection, promotes FL thrombosis and induces successful remodelling.